1996
DOI: 10.1123/pes.8.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Social Acceptability of the Polar Vantage XL for Measuring Heart Rate in Preschoolers

Abstract: Although portable heart rate (HR) monitors are commonly used to assess energy expenditure, little is known about their suitability for preschoolers. To validate the Polar Vantage XL monitor (XL), the HRs of twenty-seven 3- to 5-year-old girls and boys were measured using the XL and ECG simultaneously. During rest, values for both methods were virtually identical (ECG = 97.3 ± 7.5, XL = 97.9 ±7.2, r = .99 for lying, and ECG = 111.1 ± 16.5, XL = 110.4± 16.3 for sitting). XL nonsignificantly underestimated HR dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Further, the monitor did not interfere with the participants' physical activity movements. This finding is in agreement with Bar-Or, Bar-Or, Waters, Hirji, and Russell (1996), who found that heart rate monitors were suitable and appropriate for young children.…”
Section: Methodssupporting
confidence: 92%
“…Further, the monitor did not interfere with the participants' physical activity movements. This finding is in agreement with Bar-Or, Bar-Or, Waters, Hirji, and Russell (1996), who found that heart rate monitors were suitable and appropriate for young children.…”
Section: Methodssupporting
confidence: 92%
“…The Polar HR monitor is a valid measure of HR compared to R-R intervals from an electrocardiograph. Mean HR data from the Polar monitor is not significantly different than from an electrocardiograph, and the two methods correlate at .99 in both adults (Gamelin, Berthoin, & Bosquet, 2006) and children (Bar-Or, Bar-Or, Waters, Hirjl, & Russell, 1996;Gamelin, Baquet, Berthoin, & Bosquet, 2008). BP was measured with a Suntech 4240 monitor (Suntech 4240, Morrisville, NC).…”
Section: Measurementsmentioning
confidence: 99%
“…Heart rate (HR) telemetry has been shown to be a valid and reliable measurement of physical activity and has commonly been used in physical activity and physical education settings (Bar-Or, Bar-Or, Waters, Hirji, & Russell, 1996;Treiber et al, 1989). Student heart rate levels during each PE-lesson were measured with Polar Team System heart-rate monitors, developed by Polar Electro, Finland.…”
Section: Methodsmentioning
confidence: 99%